Corresponding Periodontal Health Status Of Orthodontic Patients: A Clinical Study (Journal of Pharmaceutical Negative Results, 2023)
The purpose of this research was to investigate whether or not orthodontic treatment has an impact on the periodontal health of young patients. From the Orthodontics department of Dental Hospital, 50 patients were chosen at random, and their gender was not taken into consideration. An examination of the periodontium was done prior to treatment, as well as after six months and following treatment. The periodontal disease index, also known as the PDI, was utilized in order to evaluate the periodontal health of the teeth that were indexed. The findings demonstrated that patients who are currently undergoing orthodontic treatment do, in fact, show signs of periodontal disease.